Short Communication: Isolation and characterization of the endophytic bacteria, and their potential as maize diseases control - endang mugiastuti; SUPRAYOGI; NUR PRIHATININGSIH; LOEKAS SOESANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Mugiastuti E, Suprayogi, Prihatiningsih N, Soesanto L. 2020. Short Communication: Isolation And Characterization Of The Endophytic Bacteria, And Their Potential As Maize Diseases Control. Biodiversitas 21: 1809-1815. Sheath blight and bacterial wilt are diseases that can reduce maize production. Biological control with the endophytic bacteria offers environmentally friendly control for these pathogens. The study aimed to isolate and characterize the endophytic bacteria morphologically and biochemically and to study their potential to control maize diseases, especially sheat blight and bacterial wilt causing pathogens. The study was conducted at the Plant Protection Laboratory, Faculty of Agriculture, Jenderal Soedirman University, from April to August 2019. The study consisted of four stages: isolation and characterization of endophytic bacteria, the antagonism test of the endophytic bacterial to R solani, the antagonism test of the endophytic bacteria to Pantoea sp., and the mechanical test of the endophytic bacteria as biological control agents and plant growth-promoting bacteria. Based on the research, four endophytic bacteria isolates have been successfully isolated, and characterized successfully and found have the potential to be developed as biopesticides to control maize disease, especially R. solani and Pantoea sp. Bacillus sp, endophytic from the root (BK.A1; BK.A3; PP.A5) and Bacillus sp. endophytic from the stem (PPD.B2) can suppress the growth of R.solani by more than 50%, have a strong antagonistic index against Pantoea sp (> 4), and can produce protease and lipase enzyme, and phosphate solubilization.